The effects of palm tocotrienol on metabolic syndrome and bone loss in male rats induced by high-carbohydrate high-fat diet. (May 2018) - Wong, Sok Kuan; Chin, Kok-Yong; Suhaimi, Farihah Hj; Ahmad, Fairus; Ima-Nirwana, Soelaiman
Graphical abstract: Highlights: Inflammation plays an important role linking metabolic syndrome and bone loss. High-carbohydrate high-fat diet induces metabolic syndrome and bone loss. Tocotrienol as single agent prevents both metabolic syndrome and bone loss. The plausible mechanism relies on the alleviation of inflammatory response. Abstract: Inflammation is a possible mediator of the relationship between metabolic syndrome (MetS) and osteoporosis. Palm tocotrienol, an anti-inflammatory agent, has been reported to exert beneficial effects for the treatment of MetS and osteoporosis individually. This study aimed to investigate the potential role of palm tocotrienol in preventing both MetS and bone loss in male rats via alleviating the inflammatory response. In this study, MetS was established in the rats fed with HCHF diet. This was accompanied by bone loss and elevated pro-inflammatory cytokine levels. Supplementation of palm tocotrienol improved MetS parameters, trabecular bone microstructure, bone strength, and reduced pro-inflammatory cytokines in the HCHF rats. A dose-dependent effect of palm tocotrienol was also observed in preventing MetS conditions. In conclusion, palm tocotrienol prevents both MetS and bone loss, possibly through its anti-inflammatory properties.